Continuity of resistance: indigenous participatory concepts in Purbalingga rural cinema culture - Syamsul Barry; Pande Made Sukerta; Martinus Dwi Marianto; T Slamet Suparno (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Purbalingga Regency, Central Java, is one area that has a unique and unique way of developing film-making. This article aims to find the concept of a participatory community approach in developing rural cinema through training/discussion programs, film production, and film screenings/Festivals from 2006 to the present. This study uses qualitative methods that include participatory, direct observation, and interviews with a data processing interactive analysis model. The results show that rural cinema encourages the empowerment of rural communities. Rural communities' high interest and participation in film activities are because the concept of cinema development comes from local cultural values (Banyumasan/Ngapak). This concept has succeeded in forming a unique, independent, and dynamic film ecosystem that can be a model for film development elsewhere